2018
DOI: 10.15244/pjoes/76791
|View full text |Cite
|
Sign up to set email alerts
|

Improving Water Productivity and Reducing Nutrient Losses by Controlled Irrigation and Drainage in Paddy Fields

Abstract: Controlled irrigation and drainage (CID) has received considerable attention as a reliable management practice for improving water quality and water productivity in rice production. This study aimed to evaluate the effects of CID on water productivity, nitrogen, and phosphorus losses in paddy fields. Treatments include alternate wetting and drying (AWD; lower limit of irrigation to-200 mm and upper limit of ponding water depth after rainfall to 60 mm), CID-I (lower limit of irrigation to-200 mm and upper limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, a constant water level throughout the growth stage of rice may be unfavorable to root growth and may affect grain yield [16] . In contrast to CD treatment, AWD can decrease irrigation volume by up to 38% with no yield reductions if implemented correctly [4] . Tan et al [53] found that AWD reduced irrigation water without a significant effect on grain yield and increased mean WUE by 16.9% compared with CD treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a constant water level throughout the growth stage of rice may be unfavorable to root growth and may affect grain yield [16] . In contrast to CD treatment, AWD can decrease irrigation volume by up to 38% with no yield reductions if implemented correctly [4] . Tan et al [53] found that AWD reduced irrigation water without a significant effect on grain yield and increased mean WUE by 16.9% compared with CD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease may be attributed to the adverse influence on the rice root system by the reduced root oxidizing power as a result of the oxygen deficiency under a high ponded water table and continuous flooding in wet and normal years [55] . In terms of economic effects, Lampayan et al [4] found that water savings can increase farm income by as much as 17% in Vietnam, 32% in the Philippines, and 38% in Bangladesh. AWD had a relatively low frequency of irrigation events, which reduced the labor costs of irrigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWM is gaining popularity in other countries of the world due to improved quality of water flowing from drained agricultural fields to surface water. The practice has been tested on research facilities in several countries including Lithuania [ 40 ], Sweden [ 41 ], Denmark [ 39 ], Italy [ 42 ], China [ 43 , 44 ], Iran [ 45 ], India [ 46 ], Japan [ 47 ], and Egypt [ 48 ]. Unfortunately, the results of experimental field studies usually include a short measurement period of CD effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for reducing water use in crop production varies significantly, from soil mulching to reducing soil evaporation [26]. In addition, the suitable application of controlled irrigation and drainage can save fresh water and reduce nutrient losses [27]. In areas where certain yields are failed to be achieved even through rational soil water management, irrigation as an agrotechnical measure may be improved.…”
Section: Introductionmentioning
confidence: 99%